(untitled) (European Journal of Pure and Applied Mathematics, 2025)
A finite modular lattice A is said to be MPP if there is an endomorphism, called an MPP endomorphism, whose the pre-period is equal to the length of A. A monounary algebra (A,f) is said to be MPP if f is an MPP endomorphism of a lattice , called an MPP corresponding lattice to (A,f). In this work, we show all MPP monounary algebras induced by endomorphisms of the direct products of two chains.